Kerajaan Haru yang Islam Berpusat di Deli Tua - Tuanku Lucman Sinar Basyarshah (Balai Arkeologi Sumatera Utara, 2008)
AbstractBased on Chinese sources, at least in the middle of 15 th AD the king and people of Haru have been Islamized. Due to historical notes capital of Haru kingdom was Deli Tua region in the upstream of Deli River (Petani River).